Functional characterisation of ABC-type metal ion uptake systems in the staphylococci - Ridley, Kristian (2004)
Previously, the sitABC operon of S. epidermidis has been shown to be regulated in response to the extracellular concentration of both iron and manganese, though the identity of the true substrate for this putative ABC-type import system remains to be determined. Through the course of these investigations, the metal binding characteristics of the substrate binding component, SitC, were investigated further. Recombinant protein was over-expressed and purified as an oligomeric form. The metal binding properties of purified SitC were studied using circular dichroism (CD) spectroscopy, which demonstrated a primary specificity for Mn2+ ions with additional lower affinities for Fe2+ and Zn2+ ions. Hill analysis showed metal ion binding proceeded with dissociation constants within the micromolar range and with the strongest degree of cooperativity with Mn2+. As only a single metal ion binding site is expected to reside within SitC this cooperativity was proposed to occur intermolecularly. Inductively coupled plasma atomic emission spectroscopy (ICP-AES) revealed dissociation between metal ions and SitC with Mn2+ almost completely dissociating, and which may be due to conformational changes required to relay the substrate(s) through the transport system. A molar ratio of bound metal ion to protein approaching 1:1, suggests SitC possesses only a single metal ion binding site. These data suggest SitABC may function primarily in manganese uptake. MntC from S. aureus is regarded as an orthologue of SitC, and which has previously been shown by mutational analysis to function solely in manganese accumulation. An amino-terminal truncate of MntC (His(6)-MntC-N) was over-expressed also in an oligomeric form and the metal binding properties compared to SitC using CD analysis. Using this method, His(6)-MntC-N demonstrated cooperative primary specificity for Mn2+, with secondary affinity for Zn2+ and Cu2+ but no evidence of Fe2+ binding was apparent. These data support the previous hypothesis that SitC and MntC are orthologous in their primary metal ion specificity, though attempts to provide confirmatory functional evidence through mutational analysis of sitABC were unsuccessful.